A novel radiation protection method for miniaturized MIMO mobile terminal antenna design based on metamaterials - Zhou, Wen-Ying; Li, Yu-Xin; Li, Wei; Lu, Mai; Xu, Jin-Jing (PloS one, 2025)
In this article, we propose an innovative approach to reduce radiation dose absorption inside human head tissues by shrinking the multiple-input multiple-output (MIMO) terminal geometric area. Initially, we employ COMSOL software to design a MIMO mobile terminal antenna that meets 2G, 3G, 4G, and 5G communication requirements. Through adding the decoupling unit, its geometric area reduces from 58 × 120 mm² to 44 × 80 mm², and its simulations and measurements indicate that the miniaturized MIMO mobile terminal antenna exhibits good radiation performance. Subsequently, we construct a head model based on standard anatomical features, including the scalp, skull, cerebrum, cerebellum, and brainstem. A comparative analysis of the specific absorption rate (SAR) across various cranial tissues, conducted before and after the antenna’s miniaturization, reveals significant reductions: maximum decreases of 85.51% in the scalp, 85.62% in the skull, 89.02% in the cerebrum, 93.04% in the cerebellum, and 88.02% in the brainstem. These findings suggest a significant decrease in the risk of electromagnetic exposure to human subjects by miniaturization. The miniaturization of the MIMO mobile terminal antenna could effectively mitigate the absorption of radiation by head tissues, thereby presenting a novel strategy for electromagnetic radiation protection.